Anaerobic fluorescent reporters for live imaging of Pseudomonas aeruginosa - Tchagang, Caetanie F.; Mah, Thien-Fah; Campbell-Valois, François-Xavier (Frontiers in Microbiology, 2023)
Pseudomonas aeruginosa thrives in the airways of individuals with cystic fibrosis, in part by forming robust biofilms that are resistant to immune clearance or antibiotic treatment. In the cystic fibrosis lung, the thickened mucus layers create an oxygen gradient, often culminating with the formation of anoxic pockets. In this environment, P. aeruginosa can use nitrate instead of oxygen to grow. Current fluorescent reporters for studying P. aeruginosa are limited to the GFP and related analogs. However, these reporters require oxygen for the maturation of their chromophore, making them unsuitable for the study of anaerobically grown P. aeruginosa. To overcome this limitation, we evaluated seven alternative fluorescent proteins, including iLOV, phiLOV2.1, evoglowBS2, LucY, UnaG, Fluorescence-Activating and Absorption-Shifting Tag (FAST), and iRFP670, which have been reported to emit light under oxygen-limiting conditions. We generated a series of plasmids encoding these proteins and validated their fluorescence using plate reader assays and confocal microscopy. Six of these proteins successfully labeled P. aeruginosa in anoxia. In particular, phiLOV2.1 and FAST provided superior fluorescence stability and enabled dual-color imaging of both planktonic and biofilm cultures. This study provides a set of fluorescent reporters for monitoring P. aeruginosa under lowoxygen conditions. These reporters will facilitate studies of P. aeruginosa in biofilms or other contexts relevant to its pathogenesis, such as those found in cystic fibrosis airways. Due to the broad host range of our expression vector, the phiLOV2.1 and FAST-based reporters may be applicable to the study of other Gram-negative bacteria that inhabit similar low-oxygen niches.